Analysis of the Analgesic Effects of Polyherbal Topical Formulations Using Hot Plate Test In Mice - Shital Shinde; Aniket J. Gavade; Saraswati P. Shinde; Sanket S. Shinde; S. M. Sarvagod; Atul R. Chopade (International Journal of Pharmacy and Analytical Research, 2026)
Background: Natural phytoconstituents have gained increasing attention for their analgesic and anti-inflammatory activities. Bioactive compounds such as curcumin, capsaicin, berberine, mangiferin, and piperine possess significant pharmacological properties and may provide safer alternatives for pain management. Objective: The present study aimed to evaluate the analgesic activity of topical formulations containing combinations of selected phytoconstituents using the hot plate model in mice. Methods: Analgesic activity was assessed using the hot plate method described by Nathan B. Eddy and Dorothy Leimbach. Swiss albino mice (25–30 g) were divided into groups (n = 4) and treated with control, test formulations (F2, R5, T4), and a standard marketed formulation. Latency time for paw licking or jumping was recorded at 0, 30, 60, 120 and 150 minutes following topical administration. Percentage pain threshold inhibition was calculated and statistical analysis was performed using GraphPad Prism. Results: All tested formulations significantly increased the latency time compared with the control group. Among the formulations, R5 (Curcumin + Capsaicin + Piperine) demonstrated the highest analgesic activity with maximum pain inhibition of 84.98%, which was comparable to the standard formulation. Conclusion: The results indicate that polyherbal formulations containing bioactive phytoconstituents possess significant analgesic activity. The synergistic interaction among these compounds may contribute to enhanced pain-relieving effects.